Answer :
Answer:
39 + 5d
Step-by-step explanation:
First multiply 5 by 9 and 5 by d then subtract 6 from 45 (which you get from multiplying 5 by 9) and you get 39 and multiply 5 by d so you get 39 + 5d
let's solve:-
[tex]⇒5(9 + d) - 6(given \: equation) \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\ \\ ⇒by \: bodmas \: rule \: distribute \: 5 \: with \: 9 \: nd \: d \\ \\⇒ 45 + 5d - 6 (subtracting \: like \: terms) \: \: \: \: \: \: \: \: \\ \\⇒ 39 + 5d \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\ \\ [/tex]